Model of Brand Image and Purchasing: Price Perception and Product Quality (Literature Review of Marketing Management) - Wydyanto Wydyanto; Andri Yandi (Journal of Accounting and Finance Management, 2020)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that influence brand image and purchasing decision, namely: price perception and product quality, a Marketing Management Literature Study. The results of this research library are that: 1) Price perception has a relationship and affects the brand image; 2) Product quality has a relationship and affects the purchasing decision; 3) Price perception has a relationship and affects the brand image; 4) Product quality has a relationship and affects the purchasing decision, and 5) Brand image has a relationship and affects the purchasing decision.